(untitled) (Latakia University Journal -Engineering Sciences Series, 2019)
يصف هذا البحث كيفية استخدام طريقة الحصول على البنية انطلاقاً من الحركة في حساب حجوم العناصر. في طريقة العمل المقترحة، تم الحصول على البيانات باستخدام هاتف نقّال أما حساب الحجم فقد تم باستخدام برنامج منخفض التكاليف وبرامج مجانية مفتوحة المصدر وحاسب شخصي. معطيات الدخل هي صور ساكنة وتسجيلات فيديو تم الحصول عليها باستخدام آلة تصوير الهاتف النقّال. وللتحقق من الطريقة، تم القيام باختبارين على عنصر منتظم الشكل وعلى عنصر غير منتظم الشكل، حجمهما معلوم. وفي كل اختبار، تم استخدام الصور وتسجيلات الفيديو في حساب الحجوم وتمت مقارنة النتائج. بالنسبة للعنصر المنتظم، فقد بيّنت النتائج أنه لا معنى للفرق بين حجمه الحقيقي والحجم المحسوب من الصور الساكنة، في حين أثرت دقة تمييز الصور المقتطعة من تسجيل الفيديو على دقة النتائج. أما في حالة العنصر غير المنتظم، فقد أثر عدم انتظام الشكل أيضاً على دقة الحجم المحسوب. من ناحية أخرى، بيّنت النتائج تأثير عدد الصور ونوع معطيات الضبط على النتائج. The article describes how the Structure-from-Motion (SfM) method can be used to calculate the volume of objects. In the proposed workflow, data is obtained using a smartphone. The volume is computed using a low-cost software and free open source software on a personal computer. The input data is still images and video frames obtained by a smart phone. To verify the method, two laboratory tests on a regular form object and irregular form object of a known volumes, have been carried out. In each test, still images and video frames were used and the results were compared. In the case of the regular object and the still images, the results showed that no significant difference was found between the real and the computed volumes. When using video frames, the results were influenced by the geometric resolution of the frames. In the case of irregular object, the irregularity of the form influenced the resulted volume. On the other hand, the results showed the effects images number and the type of control data on the results.